THE EFFECT OF DISSECT STRATEGY ON FIRST YEAR EFL UNIVERSITY STUDENTS’ WORD AWARENESS - Mohammed, Fakhir Omar (European Scientific Journal, ESJ, 2014)
The present study aims at understanding, explaining and assessing the word identification strategy, DISSECT, which has become an increasingly important skill for learning disabilities, to minimize oral reading errors made by students at the Department of English, School of Languages, University of Zahko. Giving first year students of English a previously prepared list of affixes, the students could make use of them to decode difficult and unfamiliar multisyllabic words taken from a variety of content areas. Focusing on the students’ adoption of the DISSECT strategy, the researcher followed the methods of observation and evaluation to discover the range of reading skills through word awareness on the part of the students. Depending on a number of tests, the researcher evaluated and measured students’ abilities to easily master the word awareness skills. Following some teaching instructions and practices, students were given the steps of DISSECT strategy to assess their word awareness skills. Finally, the strategy in question was measured to evaluate students’ abilities in mastering and improving the reading skills, by means of a series of t-tests, ANOVAs and multiple comparison correlations, that were programmed and output by SPSS software 17.0.